2000
DOI: 10.1111/j.1572-0241.2000.02317.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of The Rice Breath Hydrogen Test for Small Intestinal Bacterial Overgrowth

Abstract: Clinical value of the rice breath hydrogen test for detecting small intestinal bacterial overgrowth is limited. The rice breath hydrogen test is not a suitable alternative to small intestinal intubation and culture of secretions for the detection of small intestinal bacterial overgrowth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
128
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(133 citation statements)
references
References 25 publications
2
128
0
3
Order By: Relevance
“…The status of cholecystectomy is related with rapid intestinal transit. During the lactulose breath test, it is difficult to distinguish SIBO from colonic bacteria in case of rapid intestinal transit, 10,26,27 and importantly lactulose itself induces rapid small bowel transit. 28 In addition, the advantages of breath test using glucose over lactulose as the substrate for the breath test are low false positivity and superiority of diagnosing SIBO.…”
Section: Discussionmentioning
confidence: 99%
“…The status of cholecystectomy is related with rapid intestinal transit. During the lactulose breath test, it is difficult to distinguish SIBO from colonic bacteria in case of rapid intestinal transit, 10,26,27 and importantly lactulose itself induces rapid small bowel transit. 28 In addition, the advantages of breath test using glucose over lactulose as the substrate for the breath test are low false positivity and superiority of diagnosing SIBO.…”
Section: Discussionmentioning
confidence: 99%
“…Using lactulose breath tests (LBT), Pimental and colleagues showed that 78% of IBS patients had SIBO [128] and that eradication with a seven-day course of neomycin was associated with a significant reduction in symptoms [129] . However, these results are somewhat controversial, as both the accuracy of the LBT and its ability to gauge treatment response has been questioned [130][131][132][133] . More recently, Posserud and colleagues conducted a study of 162 IBS patients using cultures of jejunal aspirates to detect SIBO [134] .…”
Section: Antibioticsmentioning
confidence: 99%
“…We suspect that the bacterial overgrowth in the small intestine occurred among the subjects of "pattern A", because it results in a similar pronounced breath hydrogen excretion as that of "pattern A" in serial breath hydrogen collection (Riordan et al, 1995). Breath hydrogen test has been widely applied for diagnosing small intestinal bacterial overgrowth as a noninvasive alternative to culture of small intestinal aspirate.…”
Section: Discussionmentioning
confidence: 99%